An overview of Salmonella enterica metal homeostasis pathways during infection. (12th April 2021) - Cunrath, Olivier; Palmer, Jacob D
ABSTRACT: Nutritional immunity is a powerful strategy at the core of the battlefield between host survival and pathogen proliferation. A host can prevent pathogens from accessing biological metals such as Mg, Fe, Zn, Mn, Cu, Co or Ni, or actively intoxicate them with metal overload. While the importance of metal homeostasis for the enteric pathogen Salmonella enterica Typhimurium was demonstrated many decades ago, inconsistent results across various mouse models, diverse Salmonella genotypes, and differing infection routes challenge aspects of our understanding of this phenomenon. With expanding access to CRISPR-Cas9 for host genome manipulation, it is now pertinent to re-visit past results in the context of specific mouse models, identify gaps and incongruities in current knowledge landscape of Salmonella homeostasis, and recommend a straight path forward towards a more universal understanding of this historic host–microbe relationship. Abstract : A comprehensive overview of the importance of metal uptake and resistance mechanisms during Salmonella infections.